Urban planning sustainability metrics for Arctic cities. (30th December 2020) - DiNapoli, Benjamin; Jull, Matthew
Abstract: Changing conditions in the Arctic are prompting increased interest in measuring the performance of Arctic cities to assess challenges of urban sustainability and inform policy makers. This paper presents methods, analysis, and preliminary results from a cross-comparative study of urban planning sustainability indicators using metrics defined by the International Organization for Standardization's ISO 37120 Sustainable Cities and Communities for 46 Arctic and near-Arctic cities. The framework for evaluating urban planning indicators described in this paper establishes a multi-method approach that defines the area of the city using local statistical units and utilizes a combination of remote sensing, geospatial analysis, and statistical data collection to calculate sustainability metrics. The results of this paper reveal several city- and regional-level characteristics of the Arctic cities in this study in terms of livability, efficiency, socio-economics and sustainability.